2014
DOI: 10.1002/macp.201300774
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Assembly into Pseudopolyrotaxane Between Cyclodextrins and Biodegradable Polyphosphoester Ionomers

Abstract: The development of novel biodegradable supermolecules is of importance in designing functionalized biomaterials utilized in the field of tissue engineering and drug delivery. In this regard, the focus here is on biocompatible and biodegradable polyphosphoester ionomers, and their pseudopolyrotaxane (PPRX) formation with α‐, β‐, or γ‐cyclodextrins (CDs) is examined. Poly(2‐hydroxy‐2‐oxo‐1,3,2‐dioxaphosphorane) (PHP) is found to form a precipitate upon mixing with α‐CD in water. Also, precipitation is observed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
2
4
0
Order By: Relevance
“…Consequently, the transmittance changes of mixed aqueous solutions of γ-CD with PHEMA as a function of incubation time provided visual evidence confirming the occurrence and evalution of the self-assembly of γ-CDs with PHEMA. This observation was also consistent with studies undertaken by Yui et al…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Consequently, the transmittance changes of mixed aqueous solutions of γ-CD with PHEMA as a function of incubation time provided visual evidence confirming the occurrence and evalution of the self-assembly of γ-CDs with PHEMA. This observation was also consistent with studies undertaken by Yui et al…”
Section: Resultssupporting
confidence: 94%
“…Consequently, the transmittance changes of mixed aqueous solutions of γ-CD with PHEMA as a function of incubation time provided visual evidence confirming the occurrence and evalution of the self-assembly of γ-CDs with PHEMA. This observation was also consistent with studies undertaken by Yui et al 35 To gain insight into the particle sizes of self-aggregates of γ-CD, PHEMA, and their inclusion complexes in aqueous solutions, the DLS measurements were performed at 25 °C, and the results are illustrated in Figure 3 and Table 2. Not surprisingly, a solution of 0.40 wt ‰ γ-CD exhibited a bimodal distribution of particle sizes of aggregates, with the main peak attributed to the γ-CD aggregates with an R h,app range of 50 to 90 nm and the small one corresponding to a single free CD molecule with R h,app = ∼1 nm in a scattering angle range of 30 to 90°, which was conceived to be crucial to the formation of PPRs composing CDs and incoming linear polymers.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
“…54 Polymeric phosphodiesters have already been used as prodrugs, hydrogels and drug carriers. 51,55,56 A pseudopolyrotaxane based on biodegradable polyphosphoester ionomers obtained by ring opening polymerization has been described by Tamura et al 53 Polyrotaxane formation was only observed with α and γ-CD and the resulting polyrotaxanes formed precipitates in aqueous solution. No inclusion complexes were obtained with β-CD.…”
Section: Introductionmentioning
confidence: 99%
“…The phosphoryl group (PO) is a good proton acceptor (about 2 orders of magnitude stronger than the CO group) and forms strong hydrogen bonds with phenols and alcohols . It is established that the PO group of poly(hydroxyalkylene phosphate) participates in hydrogen bonding with POH and OH groups . Besides, poly(hydroxyoxyethylene phosphate)s are biodegradable, biocompatible, water soluble and low toxic polymers .…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] It is established that the P@O group of poly (hydroxyalkylene phosphate) participates in hydrogen bonding with PAOH and OH groups. [28][29][30] Besides, poly(hydroxyoxyethylene phosphate)s are biodegradable, biocompatible, water soluble and low toxic polymers. 31 Polyphosphoesters degraded through hydrolysis of the PAOAC ester bonds under acidic or basic conditions [31][32][33] and this can be particularly accelerated in the presence of phosphoesterase.…”
Section: Introductionmentioning
confidence: 99%